PENGGUNAAN KEKARANGAN DAN RAGAM HIAS DALAM DESAIN BANGUNAN BALI - Nyoman Ari Adnyana; Desak Made Sukma Widiyani; Frysa Wiriantari; Ni Putu Yunita Laura Vianthi (Jurnal Anala, 2024)
Balinese building design reflects its rich cultural heritage and strong traditional identity. In this design, the use of garland and decoration plays a central role in creating a unique aesthetic and expressing religious values and the natural surroundings. Carvings, such as the structures on pelinggih, provide a distinctive physical structure, while decoration, such as wood carvings and paintings, add artistic details that enrich the appearance of the building. Through this research, we explore the use of garland and decoration in Balinese building design and instill them with cultural identity and traditional values.